VD_FINDINFO Jug / 2025 / 487 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
HARCÈLEMENT PSYCHOLOGIQUE, DROIT D'ÊTRE ENTENDU, DOMMAGE, INDEMNITÉEN GÉNÉRAL, RÉSILIATION IMMÉDIATE | 321e CO, 337 al. 1 CO, 337 al. 3 CO, 337 CO, 29 al. 2 Cst., 61 LPers-VD, 9 LRECA